1999
DOI: 10.1096/fasebj.13.14.2031
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione depletion causes cytochrome c release even in the absence of cell commitment to apoptosis

Abstract: We demonstrate here that the release of mature cytochrome c from mitochondria is a cellular response to the depletion of glutathione, the main intracellular antioxidant, independently from the destiny of the cells, i.e., apoptosis or survival. On the one hand, cytosolic cytochrome c was detected in cells where the inhibition of glutathione synthesis led to glutathione depletion without impairing viability or in tight concomitance with glutathione depletion prior to puromycin-induced apoptosis. Removal of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
1
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 28 publications
6
99
1
2
Order By: Relevance
“…Previous work has shown that oxidative stress decreases intracellular GSH through efflux, and GSH efflux has been identified as a proximal mediator of apoptosis through induction and activation of BAX. 32,33 Here, inhibition of SOD activity also caused rapid depletion of intracellular GSH, consistent with increased intracellular oxidant stress ( Figure 6B). Thus, our results also link BAX activation to oxidative stress and decreased intracellular GSH in vitro.…”
Section: Effects Of Oxidative Stress On Airway Epithelial Cellsmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous work has shown that oxidative stress decreases intracellular GSH through efflux, and GSH efflux has been identified as a proximal mediator of apoptosis through induction and activation of BAX. 32,33 Here, inhibition of SOD activity also caused rapid depletion of intracellular GSH, consistent with increased intracellular oxidant stress ( Figure 6B). Thus, our results also link BAX activation to oxidative stress and decreased intracellular GSH in vitro.…”
Section: Effects Of Oxidative Stress On Airway Epithelial Cellsmentioning
confidence: 68%
“…22 Interestingly, efflux of glutathione reproducibly activates BAX and cytochrome c release in epithelial cells in vitro and is one established mechanism for induction of apoptosis. 32,33,46 In support of increased transcellular glutathione fluctuation in the upstream events leading to epithelial cell apoptosis in asthma, glutathione levels are higher than normal in the asthmatic airway lining fluid, indicating increased efflux from epithelial cells in vivo. 42,[47][48][49] An overwhelming number of studies support oxidative and nitrative processes in the pathogenesis of asthma.…”
Section: Discussionmentioning
confidence: 98%
“…It was shown that after treatment with H 2 O 2 at low concentrations, or after glutathione depletion in U937 and HepG2 cells, cytochrome c is released in the absence of apoptosis (Ghibelli et al, 1999); at the same time, Bax translocates to mitochondria, and undergo dimerization, as detected in non-reducing but denaturing electrophoresis (SDS-PAGE) (D'Alessio et al, 2005). Cell-free oxidation of cytosolic extracts with H 2 O 2 leads to disulfide dimerization.…”
Section: Bax As a Sensor Of Physico-chemical Alterationsmentioning
confidence: 99%
“…Immunoblot analysis of nuclear protein was performed using 10 g of protein isolated as described above. Release of cytochrome C into the cytosol was determined by immunoblot as described by Ghibelli et al 29 using a mouse monoclonal anti-cytochrome C antibody (PharMingen, La Jolla, CA). Membranes were blocked in Tris-buffered saline with 0.1% Tween 20 containing 5% milk (blotting grade; BioRad, Hercules, CA) at 4°C and incubated with primary antibodies at the following dilutions: p65, 1:2,000; Mch5, 1:1,000; caspase-3, 1:1,000; and cytochrome C, 1:1,000, in 0.5% milk in Tris-buffered saline with 0.1% Tween 20 for 1 to 2 hours.…”
Section: Immunoblot Analysismentioning
confidence: 99%